Acaricidal Properties of Four Neem Seed Extracts (Azadirachta indica) on the Camel Tick Hyalomma dromedarii (Acari: Ixodidae) - Gareh, Ahmed; Hassan, Dalia; Essa, Asmaa; Kotb, Saber; Karmi, Mohammed; Mohamed, Abou El-Hamd H.; Alkhaibari, Abeer Mousa; Elbaz, Elzahara; Elhawary, Nagwa M.; Hassanen, Eman A. A.; Lokman, Maha S.; El-Gohary, Fatma A.; et al. (Frontiers in Veterinary Science, 2022)
Tick infestation remains one of the major health problems that affect the productivity and comfort of camels . The control of ticks is mainly relied on using chemical acaracides. Limited information is available on the potential benefits and activity of various neem extracts on Hyalomma ticks. The present study investigated the caricidal activity of neem seed extracts at different concentrations against developmental stages of the camel ticks Hylomma dromedarii in comparison to Butox and Diazinon. The acaricidal activity of three extracts, including Hexane Extract (HE), Methyl Chloride Extract (MCE), and Methanol Extract (ME), of neem seeds (Azadirachta indica) were tested at varying concentrations of 5%, 10%, 15%, and 20% on engorged H. dromedarii female at days 1, 3, 5, 7, 12, 16, 20, 28, 37, and 43 after treatment (DPT). Interestingly, results of applying different neem seed extracts to engorged H. dromedarii female ticks showed that the most effective extract was Hexane at concentration 20%, causing 100% mortality at 1st day post application, while Methanol extract at 20% and Dichloromethane extract at 20% caused the death of all ticks at 28th day post treatment as compared to Butox® 5.0, and Dizanon-60, that resulted in mortality of all ticks at 3, 5 DPT respectively. In addition, no mortality was reported with application of Aqueous Extract (AE) which served as control group. Furthermore, neem hexane extract exhibited high efficacy against reproductive performance of female, whereas no fertility or oviposition was reported at all of its concentrations. Additionally, no hatchability occurred using all neem extracts except the aqueous extract that showing no effect. In the present study, larvae responded more rapidly to the plant extracts, whereas mortality of all larvae was recorded at 24 h after treatment with 5% hexane. Taken together, this study pointed out that the acaricidal effect of hexane extract of neem seeds was more effective, and could be economically used for controlling H. dromedarii ticks.